The Guidelines to Increase Accounting Service Efficiency in Eastern Economic Corridor (EEC) - Jokkaew, Jinda (Journal of Industrial Business Administration, 2021)
The purpose of this research is to study the guidelines to increase accounting service efficiency in Eastern Economic Corridor (EEC). Respondents are accounting staffs in the accounting office of the district EEC. Sample size: 394 persons. Research instrument used are questionnaires. SPSS Program is used to analyze the data. Result showed a very high level of comments from the accounting staffs in the accounting office of the district EEC about the guidelines to increase accounting service efficiency in ECC. Comparing the difference of average importance of the guidelines to increase accounting service efficiency in EEC, there was a significant difference at 0.05 level from experiences of key informant in term and ethics, resource management of accounting firms, monitoring and document management. On the other hand, there was no significant difference at 0.05 level in executive’s responsibility on internal quality, customer and task accounting firms from positions of key informant.